A derived ZW chromosome system in Amborella trichopoda, representing the sister lineage to all other extant flowering plants. Issue 4 (28th August 2021) - Käfer, Jos; Bewick, Adam; Andres‐Robin, Amélie; Lapetoule, Garance; Harkess, Alex; Caïus, José; Fogliani, Bruno; Gâteblé, Gildas; Ralph, Paula; dePamphilis, Claude W.; Picard, Franck; Scutt, Charlie; et al.
Summary: The genetic basis and evolution of sex determination in dioecious plants is emerging as an active area of research with exciting advances in genome sequencing and analysis technologies. As the sole species within the sister lineage to all other extant flowering plants, Amborella trichopoda is an important model for understanding the evolution and development of flowers. Plants typically produce only male or female flowers, but sex determination mechanisms are unknown for the species. Sequence data derived from plants of natural origin and an F1 mapping population were used to identify sex‐linked genes and the nonrecombining region. Amborella trichopoda has a ZW sex determination system. Analysis of genes in a 4 Mb nonrecombining sex‐determination region reveals recent divergence of Z and W gametologs, and few Z‐ and W‐specific genes. The sex chromosomes of A. trichopoda evolved less than 16.5 Myr ago, long after the divergence of the extant angiosperms.